EXAMINATION OF PULMONARY TUBERCULOSIS PATIENTS AT THE REGIONAL GENERAL HOSPITAL (RSUD) JAYAPURA - Herlando Sinaga (Jurnal Riset Kesehatan, 2019)
Tuberculosis is a disease that is directly transmitted and caused by bacteria Mycobacterium tuberculosis. Tuberculosis is an infectious disease that still causes high morbidity and mortality rates in the world. This research aims to determine the value of hemoglobin levels, platelet counts, erythrocytes, the number of neutrophils and Monocytes in positive patients with pulmonary tuberculosis who performed examinations at the Jayapura Regional General Hospital. This research was conducted for 1 month, starting from 1 May to 1 June 2018. This research is descriptive with a laboratory test approach. The population in this research included all patients who had positive pulmonary tuberculosis and the samples in this study were venous blood positive patients with pulmonary tuberculosis. The method used in this examination is flow cytometry using the hematology analyzer Sysmex XN-1000. The results of the research showed that from 20 samples, hemoglobin levels were obtained as much as 30% with normal hemoglobin levels and as much as 70% with low hemoglobin levels 70% of normal platelet value and as much as 30% high platelet count; 70% of the value of erythrocytes is normal and as much as 30% the amount of erythrocytes decreases; Neutrophils are as high as 55% while normal is 45%; and high monocytes as much as 25% and normal monocytes as much as 75%.